Epidemiological factors associated with Turtle fraservirus 1 (TFV1) in freshwater turtles in Florida, USA - Lisa A. Shender; Andrea Sylvia; Brian A. Stacy; Veronica Guzman-Vargas; Thais C.S. Rodrigues; Pedro Viadanna; Jordan A. Vann; Kylle Cahill-Patray; Thomas B. Waltzek; Kuttichantran Subramanium; Brittany Bankovich (PLoS ONE, 2025)
Turtle fraservirus 1 (TFV1) is an emerging pathogen that was first discovered in freshwater turtles in peninsular Florida (USA) in 2018. The incubation period, transmission route(s), range of virus-susceptible species, and other key epidemiological factors that pertain to this disease are still unknown. Therefore, the primary aims of this work were to 1) evaluate TFV1 infection and available metadata using an epidemiological framework and 2) summarize our findings into Florida-specific guidance for turtle morbidity (e.g., diseased condition) and mortality investigations by managers faced with limited resources. This study included several species of sick or dead freshwater turtles collected from 9 March 2018 until 5 September 2021. These collections were greatly facilitated by public reporting and submissions from state-permitted wildlife rehabilitation centers. To evaluate data obtained from different stages of a mortality investigation, we developed four datasets pertaining to field collection, necropsy findings, weather conditions, and spatial and temporal patterns. Within each dataset, we used logistic regression to determine the relative effect of available explanatory variables on the probability of a TFV1-positive PCR test result. We found that >50% (47/93) turtles tested positive for TFV1. The presence of cloacal and/or oral plaques in softshell turtles was strongly associated with TFV1-positive infection status. Furthermore, turtles that were collected from clustered mortality events (>1 turtle found sick or deceased) were more likely to test positive, with both distance and time being important defining factors. Our overall findings are compatible with a highly transmissible waterborne virus that is shed in urine or other secretions, and we suggest that future research should prioritize the study of potential direct transmission. The identification and spread of TFV1 in peninsular Florida provide further validation for the strict implementation of biosecurity practices in order to mitigate inadvertent transfer of aquatic pathogens.